Characterization of unsafe acts in dentistry (UAD) in a teaching-service institution, Medellín (Colombia), 2015-2017 - Trujillo-Hoyos, Mónica; Gil-Alzate, Diego; Agudelo-Suárez, Andrés Alonso (Revista Facultad de Odontología Universidad de Antioquia, 2018)
Introduction: the implementation of measures to improve the culture of patient safety in public and private institutions seems to require the development of epidemiological surveillance systems. This study aims to characterize unsafe acts in dentistry (UAD) according to several variables in a public oral-health higher education institution in Medellín (Colombia). Methods: longitudinal descriptive study of the UADs reported at the Universidad de Antioquia School of Dentistry during the period 2015-2017. To this end, a form was designed using the Google Docs™ tool (available upon request to the authors). The sociodemographic variables were described using absolute and relative frequencies, and chi-square statistical significance tests were used to identify differences among the variables. This study had institutional ethical approval. Results: during the study period (33 months), 541 UADs were reported, 65% of them during the year 2015. The highest frequency of UAD was reported at the Children’s clinic (84%). Also, 84% of these UADs were classified as healthcare failures. These failures were mostly reported by students, males, persons aged ≤ 24 years, and undergraduate students, and they generally occurred in male patients and persons aged ≤ 12 years. Significant differences were found (p < 0.05) between the various types of UADs and the variables considered in the analysis on the one hand, and time when the services were provided and type of clinic on the other. Conclusions: differences in the reporting of UADs were found according to the variables considered in the analysis